Output-oriented analysis of the wet mechanical processing of polyolefin-rich waste for feedstock recycling. Issue 5 (May 2018) - Kranzinger, Lukas; Pomberger, Roland; Schwabl, Daniel; Flachberger, Helmut; Bauer, Markus; Lehner, Markus; Hofer, Wolfgang
In recent years, an increasing number of studies have revealed that plastics and their components (e.g. plasticisers) pose an environmental risk. However, it is hard to imagine how our industrialised society could do without these materials, since the fields of application are manifold. One possible approach to tackle this mounting problem is the implementation of a comprehensive and well-functioning collection and recycling system. An international comparison shows that only a small proportion of the total plastics in circulation is collected and recycled. The investigations conducted under the present research project, 'Plastic Reborn', focused on both identification and analysis of the discharge paths of polyolefin-rich waste streams, under the Austrian waste management system. Another objective was determining the utilisation potential of the output fractions of these polyolefin-rich waste streams, generated from a wet mechanical processing pilot plant. Experiments have shown that the polyolefins are successfully separated from the waste streams and that a total polyolefin potential of 429, 000 t y −1 remains unexploited in the Austrian waste management system. Thus, these separated plastic fractions can make a significant contribution to the implementation of the European Circular Economy Directive. The residual fractions meet the legal and company-specific requirements for their use as solid recovered fuels in co-combustion plants.